A comparative study of geological conditions of tight oils in China and USA - Qun LUO; Yang GAO; Zeyuan ZHANG; Shichen WANG; Lan HONG; Wenyu MA; Qian XU (Shiyou shiyan dizhi, 2022)
On the basis of formulating and perfecting the definition and connotation of tight oil, a comparative study was carried out on the basin formation, hydrocarbon generation, hydrocarbon preservation and reservoir formation for 9 tight oil basins of China and 6 of USA. It was concluded that China′s tight oil has great potential, but the accumulation conditions are complex and diverse. There are 9 tight oil basins in China located in 3 tectonic areas in the eastern, middle and western parts of mainland China. Due to the combined action of the 3 plates of the Pacific, Siberia and India, the type, scale and formation of tight oil basins as well as the generation, preservation and enrichment of hydrocarbon are varied and have regular change trends among the three tectonic areas. From the western tectonic area to the central and then to the eastern one, the distribution scale of tight oil changes from small to large and then to middle, and the number of tight oil distribution horizon decreases from the Upper Permian to the Middle Jurassic and finally to the Lower Cretaceous. The generation conditions of tight oil changed from bad to good and to relatively good. The types of tight oil reservoirs change from multiple and complex to relatively complex and then to relatively simple. The reservoir performance of tight oil reservoirs changes from relatively good to relatively poor and to relatively good, while permeability changes from relatively high to relatively low and to relatively high. The conditions of tight oil migration and accumulation change from relatively poor to good and to relatively good, and the types of tight oil reservoirs change from more to less and back to more. The exploration and development potential of tight oil is the largest in the western tectonic area, followed by the central and then the eastern one. The tight oil basins and tight oil accumulations in China and USA have both commonalities and obvious differences. The fundamental reasons for the differences are the stability of structures and the heterogeneity of sedimentary facies. The tight oil basins in China have poorer tectonic stability and continental deposition, while the tight oil basins in USA have better structural stability and marine deposition. As a result, the hydrocarbon generation capacity of tight oil basins in China is worse than that in USA, but the reservoir conditions are generally better than those in USA. The accumulation mechanism and model of tight oil enrichment in China are more complex than those in USA. The quality of tight oil in USA is generally better than that in China. The size of tight oil basins in USA and the exploration and development potential of tight oil are greater than those in China.